AUGMENTED REALITY BASED INFORMATION TECHNOLOGY FOR OBJECTS 3D MODELS VISUALIZATION (Computer systems and information technologies, 2023)
At the current stage of IT industry development, augmented reality is of interest both from the side of science and from the business side, since it is an advanced and newest tool for introducing a new immersive user experience. Today there are plenty ready-to-use applications that use AR for business, educational, medical and other purposes. Augmented Reality is currently one of the most popular upcoming technologies most commonly known for its use within games and advertising. By combining three-dimensional modelling with augmented reality, it could be possible to obtain new user friendly applications for the representing 3D models of objects in real time and in real size. The topic of research in the field of augmented reality is currently relevant both for science and for the business industry.The paper proposes a multifunctional information system for three-dimensional models visualization in augmented reality, which is implemented in the form of a cross-platform mobile application. The proposed information system uses a device camera as a mean of object visualization and provides quick reproduction of the selected from the application`s database model in augmented reality in real size and in real time.The developed application works quite well, has a user friendly and intuitive interface and allows user to add own models, that makes this tool multipurpose.Test 3D models have been created for conducting experiments for verification the proposed information system operation.The further efforts of the authors will be directed to improving the existing algorithms for extending the current functionality of the proposed tool for 3D objects models visualization in augmented reality and application of the developed tool for real-life needs, such as digitization and visualization of museum exhibits and archaeological artifacts of Khmelnytskyi region.
Keywords: information system; artificial (augmented) reality; visualization; mobile application; 3D model